An example of use of gas turbine engine compressor, which has been mastered in production and has good characteristics in a new product project - A. V. Grekhnev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The development of a new gas turbine engine requires a lot of time and money spent on the design and testing its compressor, which has been shown as the most complex and time-consuming assembly unit of the engine. This article examines the potential application of the industry-developed engine compressors in the designs of a new turbojet engine and a gas turbine compressor. The comparative analysis of the ideal cycles of an augmented turbojet engine and a turbojet engine with a high-temperature combustor is made. The advantage of the turbojet engine with a high-temperature combustor configuration over the augmented turbojet engine configuration is shown. The high rates of jet-pipe gas velocity make a turbojet engine with a high-temperature combustor suitable for supersonic cruise products.